Mathematics knowledge competency of prospective secondary mathematics teachers in the province of Isabela - Aguinaldo, Clemente M., Jr. (Animo Repository, 2006)
This study was conducted with the aim of determining the mathematics knowledge competency of prospective secondary mathematics teachers in the province of Isabela. The instruments used in the gathering of data included the questionnaire on respondents' non-intellective and intellective characteristics and the researcher-developed Mathematics Knowledge Competency Test. The findings of study showed that the prospective teachers have a satisfactory competency level in mathematics. It also showed that the age, the number of seminars or trainings attended and the average grade in secondary mathematics are significantly related to their knowledge competency.